1993
DOI: 10.1016/0899-3289(93)90007-x
|View full text |Cite
|
Sign up to set email alerts
|

The female weight-control smoker: A profile

Abstract: Hypothesizing the existence of a subgroup of female smokers for whom nicotine masks, and abstinence unmasks, a tendency toward hyperphagia and perhaps even subthreshold disordered eating, we compared female "weight-control smokers" (WC; n = 46) and "non-weight-control smokers" (NWC; n = 52) on smoking- and eating-related variables. We also examined the relationship between weight-control smoking and withdrawal symptomatology during 48-hours of nicotine abstinence (n = 23). Although WC were not more depressed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 28 publications
4
52
0
2
Order By: Relevance
“…However, the increased smoking behaviour of the HDHR women could also function as a weight control strategy. Copeland and Carney (39) and Pomerleau et al (40) both found that women with high Disinhibition and high Restraint scores reported higher expecta-tions of improved appetite and weight control from smoking than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased smoking behaviour of the HDHR women could also function as a weight control strategy. Copeland and Carney (39) and Pomerleau et al (40) both found that women with high Disinhibition and high Restraint scores reported higher expecta-tions of improved appetite and weight control from smoking than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…26 Female smokers who score high on a scale of smoking as a weight control tool may be particularly susceptible to weight gain when staying abstinent. 27,28 Although female smokers seem to accept weight gain after quitting less than male smokers, 29 little is known about gender differences in the increase of BMI after smoking cessation from general population studies. 4 Altogether, evidence is conflicting, and there are different explanations of weight changes related to changes in smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous studies from high-income countries Pomerleau et al 1993;Weekley et al 1992). Evidence suggests that weight-control smokers have low efficacy in managing their food intake especially while dealing with negative emotions (Pinto et al, 1999).…”
Section: Discussionsupporting
confidence: 82%